The role of all‐payer claims databases to expand central cancer registries: Experience from Colorado. (15th November 2021) - Perraillon, Marcelo C.; Liang, Rifei; Sabik, Lindsay M.; Lindrooth, Richard C.; Bradley, Cathy J.
Abstract: Objective: To evaluate the quality of a multiyear linkage between the Colorado all‐payer claims database (APCD) and the Colorado Central Cancer Registry. Data sources: Secondary 2012–2017 data from the APCD and the Colorado Cancer Registry. Study design: Descriptive analysis of the proportion of cases captured by the linkage in relation to the cases reported by the registry. Data collection/extraction methods: We used probabilistic linkage to combine records from both data sources for all patients diagnosed with cancer. Results: We successfully linked 93% of the 146, 884 patients in the registry. Approximately 63% of linked patients were perfect matches on five identifiers. Of partial matches, 81.6% were matched on four identifiers with missing or partial Social Security Numbers. The linkage rate was lower for uninsured patients at diagnosis (74.7%) or patients with private plans (89.4%) but close to 100% for Medicare and Medicaid enrollees. Most of the 29% of patients who did not have claims at the time of diagnosis were covered by private plans that may not submit claims. Conclusions: APCD‐registry linkages are a promising source of data to conduct population‐based research from multiple payers. However, not all payers submit claims, and the quality of the data may vary by state.